2021
DOI: 10.1016/j.prosdent.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Outcome measures in facial prosthesis research: A systematic review

Abstract: Statement of problem. Facial prosthesis research uses a wide variety of outcome measures, which results in challenges when comparing the effectiveness of interventions among studies. Consensus is lacking regarding the most appropriate and meaningful outcome measures to use in facial prosthesis research to capture important perspectives. Purpose. The purpose of the systematic review was to identify and synthesize outcome measures used in facial prosthesis research. Material and methods. Electronic searches were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 75 publications
(200 reference statements)
0
19
0
Order By: Relevance
“…Overall, the available literature indicates favorable long-term outcomes with facial prostheses 3,93,94 . However, significant variability in the choice of outcome measures in these studies makes it challenging to assess objective functional outcomes across studies 95 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the available literature indicates favorable long-term outcomes with facial prostheses 3,93,94 . However, significant variability in the choice of outcome measures in these studies makes it challenging to assess objective functional outcomes across studies 95 …”
Section: Resultsmentioning
confidence: 99%
“…3,93,94 However, significant variability in the choice of outcome measures in these studies makes it challenging to assess objective functional outcomes across studies. 95 Regarding VCA, Lantieri et al 96 reported improvements in quality of life for all 6 face transplant recipients at an average of 6 postoperative years. Sensory and motor recovery reached their final results at 18 months of follow-up, when the orbicularis oris muscle recovery allowed for complete function of the mouth with oral competence.…”
Section: Cost Analysis Associated Complications Functional Outcomementioning
confidence: 99%
“…Over the past 40 years, maxillofacial prosthesis research has concentrated on patient-reported outcome measures. This comprises the lifelong maintenance and replacement of maxillofacial prostheses (Jablonski et al, 2021). The manufacturing of these artificial or alloplastic prostheses with biomaterials permits the reconstruction of lost substance in the head and neck region, thus providing patient rehabilitation and restoring anatomy, function, and esthetics, in addition to social reintegration and improved quality of life (Caxias et al, 2019;Goiato et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in facial features can affect patient self-awareness, emotional stability, and personality traits. 1,2 Facial prosthetics are a viable alternative if esthetic and functional demands are not surgically met. [3][4][5] Such prostheses improve patient appearance and their rehabilitation, and reduce surgical and hospital stays and associated costs.…”
mentioning
confidence: 99%
“…[6][7][8][9] Consequently, patient's quality of life (QoL), mental health, and satisfaction are significantly enriched. 2 Prosthesis comfort, color, fit, maintenance, aesthetics, cost, and retention efficiency affect patient's opinions and attitudes toward its acceptance or rejection. [10][11][12][13] Their perception is also affected by their rehabilitation journey, construction procedures, clinician confidence, and resource availability.…”
mentioning
confidence: 99%